Clinic, courtroom or (specialist) committee: in the best interests of the critically Ill child?. Issue 7 (7th June 2018) - Huxtable, Richard
Abstract : Law's processes are likely always to be needed when particularly intractable conflicts arise in relation to the care of a critically ill child like Charlie Gard. Recourse to law has its merits, but it also imposes costs, and the courts' decisions about the best interests of such children appear to suffer from uncertainty, unpredictability and insufficiency. The insufficiency arises from the courts' apparent reluctance to enter into the ethical dimensions of such cases. Presuming that such reflection is warranted, this article explores alternatives to the courts, and in particular the merits of specialist ethics support services, which appear to be on the rise in the UK. Such specialist services show promise, as they are less formal and adversarial than the courts and they appear capable of offering expert ethical advice. However, further research is needed into such services – and into generalist ethics support services – in order to gauge whether this is indeed a promising development.